2012
DOI: 10.5209/rev_rced.2012.v23.n2.40039
|View full text |Cite
|
Sign up to set email alerts
|

La teoría del aprendizaje social como modelo explicativo de la violencia filio-parental

Abstract: Resumen En contra de lo que se mantenía hasta la década de los 70 del siglo pasado, el contexto familiar es el más violento, puesto que en éste puede darse la violencia parento-filial, en la pareja, entre hermanos y la violencia filio-parental. En este artículo nos centramos en la violencia de los adolescentes contra sus progenitores siendo el primer objetivo delimitar y definir tanto el término de la violencia familiar como el de la filio-parental para lograr comprender algunas de las causas que consigan expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
(36 reference statements)
1
3
0
1
Order By: Relevance
“…The results showed that adolescents engaged in APV reported higher levels of strictness and supervision both in paternal and maternal parenting. Furthermore, they reported more indifference and less affect, acceptance, and involvement in childrearing only in the maternal parenting style (Aroca-Montolío et al, 2012;Contreras and Cano, 2014;Calvete et al, 2015;Ibabe, 2015). The results corroborated the literature regarding the importance of mother positive parenting as a protective factor (Kawabata et al, 2011), however, they do not support this relationship for a father parenting style, giving more relevance to the mother's one.…”
Section: Discussionsupporting
confidence: 47%
“…The results showed that adolescents engaged in APV reported higher levels of strictness and supervision both in paternal and maternal parenting. Furthermore, they reported more indifference and less affect, acceptance, and involvement in childrearing only in the maternal parenting style (Aroca-Montolío et al, 2012;Contreras and Cano, 2014;Calvete et al, 2015;Ibabe, 2015). The results corroborated the literature regarding the importance of mother positive parenting as a protective factor (Kawabata et al, 2011), however, they do not support this relationship for a father parenting style, giving more relevance to the mother's one.…”
Section: Discussionsupporting
confidence: 47%
“…The risk and protection factors identified were both varied and fairly non-specific (Hong et al, 2012;Kennair & Mellor, 2007;Morán Rodríguez et al, 2012), being linked to domestic violence (Holt, 2016;Miles & Condry, 2015Wilcox, 2012) or social learning theory (Aroca-Montolío, Bellver Moreno, & Alba Robles, 2012), and although some theoretical hypotheses are confirmed by certain results, none are able to explain all the findings reported.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, since violence and more specifically VFP is a relational phenomenon, we must not fail to point out that it is influenced by the cultural context whose nuance is evident in the various connotations that society attributes to it according to role, age or gender of those involved (Abadías, 2019) as well as being the result of cultural constructions modeled according to the social learning approach (Aroca-Montolío et al, 2012) that are transmitted transgenerationally (Abadías, 2015).…”
Section: Introductionmentioning
confidence: 99%